Effects of proton pump inhibitors and histamine-2 receptor antagonists on response to fidaxomicin or vancomycin in patients with Clostridium difficile-associated diarrhoea - Thomas Louie; Karl Weiss; Mark A Miller; Kathleen Mullane; Derrick W Crook; Sherwood L Gorbach (BMJ Open Gastroenterology)
Objective It has been established that use of proton pump inhibitors (PPIs) is associated with an increased risk of acquiring Clostridium difficile-associated diarrhoea (CDAD). However, it is not known whether the use of PPIs or histamine-2 receptor antagonists (H2RAs) concurrently with CDAD-targeted antibiotic treatment affects clinical response or recurrence rates.Design In two phase 3 trials, patients with toxin-positive CDAD were randomised to receive fidaxomicin 200 mg twice daily or vancomycin 125 mg four times daily for 10 days. Only inpatients with CDAD (due to complete medication record availability) were included in this post hoc analysis: 701 patients, of whom 446 (64%) used PPIs or H2RAs during study drug treatment or follow-up. Baseline factors that were statistically significant in univariate analyses were analysed in multivariate analyses of effects on clinical response and recurrence.Results Multivariate analysis showed that leukocytosis, elevated creatinine and hypoalbuminemia, but not PPI or H2RA use, were significant factors associated with poor clinical responses. Treatment group was the single significant predictor of recurrence; the probability of recurrence after fidaxomicin therapy was half that following vancomycin therapy.Conclusions Acid-suppressing drugs, used by nearly two-thirds of inpatients with CDAD, did not worsen clinical response or recurrence when used concurrently with fidaxomicin or vancomycin. Therefore, development of CDAD does not require discontinuation of anti-acid treatment in patients who have an indication for continuing PPI or H2RA therapy, such as gastro-oesophageal reflux disease and risk of gastrointestinal bleed.